2018
DOI: 10.1007/s10905-018-9666-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Plasticity in Probing by Diaphorina citri (Hemiptera, Liviidae): Ingestion from Phloem Versus Xylem is Influenced by Leaf Age and Surface

Abstract: Diaphorina citri is a major pest of citrus because it transmits Candidatus Liberibacter asiaticus, a phloem-limited bacterium that putatively causes Huanglongbing (HLB). The disease moves slowly through a tree, and the vector facilitates further within-tree movement via transmission of the pathogen. However, this only happens when D. citri stylets contact the phloem, to inoculate bacteria during phloem salivation and acquire bacteria during phloem sap ingestion. Behavioral changes in D. citri associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
0
30
1
Order By: Relevance
“…For instance, in our study the CLso-infected group salivated significantly more by comparison to the non-infected group but the reverse was seen in other psyllid studies (Sandanayaka et al 2014;Antolinez et al 2017a, b;Killiny et al 2017). This could be explained by different recording periods (from 5 to 24 h) used in different studies which may have influenced the results as shown in (Sandanayaka et al 2017), and other factors like the age of the plant and the type of leaf (Luo et al 2015a, b;Ebert et al 2018), the pathogen titre in the plant or the insect, pathogen genotype and insect age. The molecular interactions that mediate feeding changes are not fully characterized or known for many pathosystems but, with the advent of functional genomics more pathways are being discovered that point out the important role that pathogen related proteins have on the vectors' phenotypic changes (Tamborindeguy et al 2017;Sackton 2018;Mauck et al 2019;Sugio et al 2015;Bernardo and Singer 2017).…”
Section: Probing Behaviour Of Clso-infected and Non-infected B Cockecontrasting
confidence: 42%
“…For instance, in our study the CLso-infected group salivated significantly more by comparison to the non-infected group but the reverse was seen in other psyllid studies (Sandanayaka et al 2014;Antolinez et al 2017a, b;Killiny et al 2017). This could be explained by different recording periods (from 5 to 24 h) used in different studies which may have influenced the results as shown in (Sandanayaka et al 2017), and other factors like the age of the plant and the type of leaf (Luo et al 2015a, b;Ebert et al 2018), the pathogen titre in the plant or the insect, pathogen genotype and insect age. The molecular interactions that mediate feeding changes are not fully characterized or known for many pathosystems but, with the advent of functional genomics more pathways are being discovered that point out the important role that pathogen related proteins have on the vectors' phenotypic changes (Tamborindeguy et al 2017;Sackton 2018;Mauck et al 2019;Sugio et al 2015;Bernardo and Singer 2017).…”
Section: Probing Behaviour Of Clso-infected and Non-infected B Cockecontrasting
confidence: 42%
“…This study evaluates, for the first time, the feeding behavior of T. erytreae by EPG in citrus and carrot plants, although this characteristic has been studied in other nearby species, such as T. apicalis, B. cockerelli, B. trigonica and B. tremblayi and for other vectors of HLB, such as Diaphorina citri [45,[55][56][57][58][59]. It is worth emphasizing that T. erytreae feed readily on citrus plants because four individuals reached the phloem in citrus, and for five times, the duration of each event was longer than 10 min; however, in our EPG assay there were no significant differences in the number or duration of E1 and E2 in citrus and carrot plants.…”
Section: Discussionmentioning
confidence: 99%
“…A fully young expanded leaf of sour orange seedlings (which facilitates EPGs) was used, but it has been shown in previous studies that the leaf stage of citrus plants plays an important role in feeding behavior and overall in the case of T. erytreae, which has a strong preference to feed on young sprouts [60]. Studies carried out with D. citri showed that it prefers to ingest from the phloem of immature leaves but from the xylem of mature leaves [59]. The citrus species used in our assay was sour orange, a frequent host of T. erytreae in the North of the Iberian Peninsula (Portugal and Spain) as ornamental tree in private and public gardens, where damages and frequency of infestation by this pest have been previously reported [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of fluorescence in the gut of D. citri after feeding on FL-penicillin-treated plants suggests that the compound was present in the vascular tissue of these plants. Sap-sucking insects such as D. citri, ingest from the phloem and xylem sap of plants [22]. Interestingly, in addition to fluorescence, we observed malformation of the guts of D. citri that consumed the FL-penicillin.…”
Section: Discussionmentioning
confidence: 84%